Reinforcing Bricks with Natural Fibres: A Review - Jen Hua Ling; Yong Tat Lim; Wen Kam Leong; How Teck Sia (Journal of Civil Engineering, 2024)
Natural fibres are biomass waste that agriculture generates in abundance. Lacking environmental awareness, biomass waste is often improperly disposed of. This raises environmental concerns. Natural fibres might be used as building materials, such as bricks. This might be a viable alternative for sustainable development. In this study, articles on the use of natural fibres in bricks are reviewed. The purposes were to study their influence on the structural behaviour of fibre-reinforced bricks and to identify their prospects and challenges. Natural fibres were found to reduce the brick's density, drying shrinkage, thermal conductivity, and workability. They boosted the compressive, tensile, flexural, and tensile splitting strengths, as well as the water absorption capacity. Natural fibres can only be used in limited amounts in bricks, usually less than 5%. This prevents significant strength loss and excessive water absorption. This study points out the drawbacks of natural fibres, such as inconsistent properties, dimensional changes, combustibility, decay susceptibility, and microbiological growth susceptibility. These shortcomings should be addressed before commercialising fibre-reinforced bricks. To overcome the problems, natural fibres may need to be carefully screened and treated before being used in bricks.